Criterio clínico para la evaluación cualitativa de la morfología en restauraciones dentales: revisión narrativa (2022)
In this research, a narrative bibliographical review was carried out to identify indices or codes that evaluate the morphological characteristics of dental restorations. The research question was established: Is there or not in the scientific literature a tool that measures the morphology of the restorations present in the teeth? Then the search was carried out in the following databases: Pubmed, Scopus preview, Proquest, science direct, Cochrane library (see Table 1), having as inclusion factors, dentistry subject area, without time limit and later from no. to find publications that met the research objectives and to tabulate the studies in a search matrix, studies from the year 2000 were taken into account.